2011
DOI: 10.1007/s10549-011-1517-z
|View full text |Cite
|
Sign up to set email alerts
|

Common genetic variation in adiponectin, leptin, and leptin receptor and association with breast cancer subtypes

Abstract: Adipocytokines are produced by visceral fat, and levels may be associated with breast cancer risk. We investigated whether single nucleotide polymorphisms (SNPs) in adipocytokine genes adiponectin (ADIPOQ), leptin (LEP), and the leptin receptor (LEPR) were associated with basal-like or luminal A breast cancer subtypes. 104 candidate and tag SNPs were genotyped in 1776 of 2022 controls and 1972 (200 basal-like, 679 luminal A) of 2311 cases from the Carolina Breast Cancer Study (CBCS), a population-based case–co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
2
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 67 publications
3
49
2
1
Order By: Relevance
“…Adiponectin 45T/G and 276T/G gene polymorphisms are of gene polymorphisms associated with breast cancer (8,27,28). In a study by Al Khaldi et al (27), the adiponectin gene 45T>G was found more frequently in patients with breast cancer in Kuwait, and the adiponectin gene was considered to predispose for breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Adiponectin 45T/G and 276T/G gene polymorphisms are of gene polymorphisms associated with breast cancer (8,27,28). In a study by Al Khaldi et al (27), the adiponectin gene 45T>G was found more frequently in patients with breast cancer in Kuwait, and the adiponectin gene was considered to predispose for breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The frequencies of LEPR polymorphisms also were different in previous reports. The frequencies of Lys109Arg wild-type (A) were 31.52%, 35.2%, 18.09% and Gln223Arg were 51.94%, 58.6%, 8.9% in whites and African American (Nyante et al, 2011), Caucasian (Teras et al, 2009) and Asian (Woo et al, 2006;Liu et al, 2007) normal population, respectively. In our study, the frequencies of Lys109Arg and Gln223Arg wild-types were 20.5% and 15.22% in controls, which was similar to Asian population.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in the adipokine levels affect cell proliferation, apoptosis and invasive growth of cancer cells (8). The adipokines produced by visceral adipose tissue have been shown to be associated with the risk and the progression of breast cancer (9,10). Therefore, elucidating the genes that regulate visceral adipose tissue accumulation and the adipokine network is important to understand the progression of visceral adipose tissue-related diseases further.…”
Section: Introductionmentioning
confidence: 99%